Implementasi Load Balancer Berdasarkan Server Status Pada Arsitektur Software Defined Network (SDN) - Lalu Fani Islahul Ardy; Aditya Bhawiyuga; Widhi Yahya (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
One of the problems in computer network is load balancing. The emergence of Software Defined Network (SDN) architecture is expected to be a new paradigm in addressing issues related to load balancing on traditional networks. The flexibility gained from separation between control plane and data plane on the SDN architecture makes it feasible to develop technologies that hard to implement on traditional networks. In this research, a load balancing algorithm is developed based on the SDN architechture. An SDN controller that is connected to an SDN switch will sends messages to each server based on the specified time interval to get the CPU and memory utilization and response time from each server. Those parameters are used to determine the load of each server. The SDN switch will then split request from client to server with smallest load. Load balancing algorithm's performance will then be compared to similar algorithms on server clusters with same specification (homogeneous) and server clusters with different specifications (heterogeneous). The result found that the proposed algorithm is able to distribute requests from clients to servers based on status of the server and perform better than similar algorithms on server clusters with different spesifications (heterogeneous).